2019
DOI: 10.2147/tcrm.s194921
|View full text |Cite
|
Sign up to set email alerts
|

<p>Drug-related problems in patients with rheumatoid arthritis</p>

Abstract: BackgroundRheumatoid arthritis (RA) patients are at risk of acquiring drug-related problems (DRPs). However, there has been a lack of studies on DRPs in patients with RA up to now.MethodThis retrospective study was conducted in a tertiary hospital in Malaysia from January 2012 to December 2017 with the purpose of assessing DRPs in RA patients and factors associated with its occurrence. A total of 200 patients who had received pharmacological treatment for RA were enrolled in this study. Assessment of DRPs was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 69 publications
5
31
2
2
Order By: Relevance
“…Some studies have reported risk factors of adverse drug reactions or adverse events [32][33][34]. Other studies have described risk factors of potential DRP in specific patient populations, such as a study in a retrospective cohort of 200 patients with rheumatoid arthritis that identified polypharmacy, multiple comorbidities, hyperlipidaemia, renal failure and osteoarthritis as risk factors [35], and a prospective study conducted in 842 patients hospitalized in cardiology wards that concluded that female sex, first hospital admission and each additional medication received increased the risk factors of DRP [25].…”
Section: Plos Onementioning
confidence: 99%
“…Some studies have reported risk factors of adverse drug reactions or adverse events [32][33][34]. Other studies have described risk factors of potential DRP in specific patient populations, such as a study in a retrospective cohort of 200 patients with rheumatoid arthritis that identified polypharmacy, multiple comorbidities, hyperlipidaemia, renal failure and osteoarthritis as risk factors [35], and a prospective study conducted in 842 patients hospitalized in cardiology wards that concluded that female sex, first hospital admission and each additional medication received increased the risk factors of DRP [25].…”
Section: Plos Onementioning
confidence: 99%
“…One notable underestimation of ADRs in the SmPC concerned nausea associated with oral methotrexate use. Previous studies indicate that nausea is one of the most frequently occurring ADRs in oral methotrexate use in inflammatory arthritis [25,26], whereas Dhir et al [2012, 27] found that the estimated frequency of nausea in oral methotrexate users in RA routine practice patients is 21.8%. This is in line with our findings in RWD with an estimated incidence of 15.8%, implying that nausea in oral methotrexate use is 'very common' (≥10%).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic database supported analysis of DDIs in the therapy of inflammatory joint diseases was carried out. Drug-related problems in RA patients like drug-choice, dosing, drug use and drug interaction problems were generally discussed by Ma et al [3]. A further study was found focusing on the quantification of polypharmacy in RA patients and investigating the interaction risk of these patients [4].…”
Section: Discussionmentioning
confidence: 99%
“…This mandatory long-term polypharmacy can result in potentially harmful drug-drug interactions (DDIs). A considerable amount of literature is available on the risk of potential interactions of single drug combinations [3][4][5][6][7][8] but to our knowledge there is no detailed review on the whole range of drugs used for managing inflammatory joint diseases.…”
Section: Introductionmentioning
confidence: 99%